Comparison between Peroneus Longus Tendon Autograft Versus Hamstring Tendon Autograft for Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-Analysis - Anak Agung Ngurah Bagus Surya Darma; I Gusti Ngurah Wien Aryana (Indonesian Journal of Global Health Research, 2025)
Peroneus longus tendon (PLT) autografts offer a promising alternative to hamstring tendon (HT) autografts in ACL reconstruction, addressing limitations like donor site morbidity and insufficient graft material. This systematic review compares clinical outcomes, highlighting PLT comparable effectiveness and potential advantages, supporting its use as a viable option for ACL repair.Material & Methods: This systematic review compared PLT and HT autografts in ACL reconstruction, assessing clinical trials via PRISMA guidelines and robust statistical methods to evaluate outcomes, study quality, and heterogeneity.Results: Four studies met the inclusion criteria for qualitative and quantitative synthesis. The analysis revealed a statistically significant improvement in International Knee Documentation Committee (IKDC) scores for PLT autografts compared to HT autografts (p < 0.0001; MD=3.16; 95% CI=2.00, 4.32). Lysholm scores showed no significant difference between the two groups (p = 0.95; MD=1.56; 95% CI=0.03, 3.09). PLT autografts demonstrated similar knee laxity outcomes and graft survival rates to HT autografts, with minimal donor site complications. Conclusions: PLT autografts offer a promising alternative to HT autografts in ACLR, providing comparable functional outcomes and graft survival rates. The use of PLT may also mitigate potential donor site complications associated with intra-knee graft harvesting.